Pengembangan Media Pembelajaran Video Animasi Berbasis Aplikasi Canva terhadap Kemampuan Menulis Teks Negosiasi di Kelas X SMA Negeri 1 Palembang - Putri Noviatami; Misriani Misriani; Darwin Effendi (Departement of Mathematics Education, 2024)
This study aims to develop animated video learning media based on the Canva application on the ability to write negotiating texts for class X SMA Negeri 1 Palembang and to describe students' responses to learning media. This type of research is Research and Development (R&D) with the ADDIE development model through the stages of Analysis, Design, Development and Implementation. Data collection techniques used observation, validation sheets, student questionnaires and documentation. The results of the validation research from media experts obtained 90% with a very valid category, material expert validation obtained a value of 95% with a very valid category and validation by linguists obtained a value of 95%. The recapitulation of the three validations obtained an average value of 93% with a very valid category. In the small group test stage conducted by 5 students, a score of 90% was obtained in the very good category. At the field test stage, 30 students obtained a score of 95% in the very good category. The recapitulation of the two stages of the student response trials was 92% in the very good category. So, it can be concluded that the animated video learning media developed is included in the very good category as a learning medium.